Diseño del campus ecológico para la carrera de ingeniería de medio ambiente en la hacienda ceypsa, provincia de Cotopaxi, periodo 2013-2014 - Quishpe Cushicondor, Gabriela Nataly (2015)
The main goal of this research is design the ecological campus for the Environmental Engineering Career in CEYPSA, in order to make a good use of renewable resources such as water, air and soil. The identified disadvantages were the inappropriate renewable resources usage around the area and a lack of classrooms for the career. For this reason a field study has been done in order to collect information about the place, which allows to elaborate an initial diagnosis in the area’s study and collect necessary data for the spaces distribution and the project establishment in the field. The design was done applying the NEC-2011 standards force in Ecuador. As an initial point we started with a general topographic survey at CEYPSA and a particular survey of the study area, it was carried out the spaces distribution according to the available resources in the area such as water, air, soil and rain; subsequently we elaborated the architectural plans with their respective facades and cuts whose software was ETABS and the structure was modeled for obtaining….